Outpatient Antibiotic Prescribing Practices for Uncomplicated Urinary Tract Infection in Women in the United States, 2002–2011. (2nd August 2016) - Kobayashi, Miwako; Shapiro, Daniel J.; Hersh, Adam L.; Sanchez, Guillermo V.; Hicks, Lauri A.
Abstract : During 2002–2011, fluoroquinolones were the most frequently prescribed antibiotic class for women aged ≥18 years with a diagnosis of uncomplicated urinary tract infection. Outpatient antibiotic stewardship initiatives should include efforts to reduce overuse of fluoroquinolones for uncomplicated UTI. Abstract: Background.  Urinary tract infection (UTI) is one of the most common diagnoses leading to an antibiotic prescription for women seeking ambulatory care. Understanding current national outpatient antibiotic prescribing practices will help ongoing stewardship efforts to optimize antibiotic use; however, information on recent national outpatient antibiotic prescribing trends for UTI is limited. Methods.  We analyzed the National Ambulatory Medical Care and National Hospital Ambulatory Medical Care Survey datasets from 2002 to 2011. Outpatient visits of women aged ≥18 years with a diagnosis of uncomplicated UTI were included for analysis. We conducted weighted descriptive analyses, examined time trends in antibiotic prescribing, and used multivariable logistic regression to identify patient and provider factors associated with fluoroquinolone prescribing. Results.  A total of 7111 visits were identified. Eighty percent of visits resulted in an antibiotic prescription; fluoroquinolones were the most frequently prescribed antibiotics throughout the study period (49% overall). Older patients (adjusted odds ratio [AOR] for adults aged ≥70 years = 2.5; 95% confidence interval [CI], 1.6–3.8) and patients treated by internists (AOR = 2.0; 95% CI, 1.1–3.3) were more likely than younger patients and those treated by family practitioners to receive fluoroquinolones. Outpatient visits in the West US Census region were less likely to be associated with fluoroquinolone prescribing (AOR = 0.6; 95% CI, .4–1.0) compared with visits in the Northeast. Conclusions.  Fluoroquinolones were the most frequently selected antibiotic treatment for uncomplicated UTI in women during the study period. Outpatient antibiotic stewardship initiatives should include efforts to reduce overuse of fluoroquinolones for uncomplicated UTI.